Environmental factors determining growth of salamander larvae: A field study. Issue 3 (1st June 2015) - Limongi, Laura; Ficetola, Gentile Francesco; Romeo, Giuseppe; Manenti, Raoul
Abstract: Larval growth and survival of organisms are strongly influenced by abiotic and biotic factors, as demonstrated by experimental studies performed under controlled laboratory or semi-natural conditions. Even if they have many advantages, experiments cannot cover the full complexity of natural conditions and field studies are needed for a better understanding of how environmental variation determines growth and development rate. Fire salamander Salamandra salamandra females give birth to larvae in a variety of habitats, both epigean and subterranean. In caves, salamander larvae successfully grow and metamorphose, but their growth is more than three times longer than in epigean streams and factors determining these differences require investigation. We performed a field study to understand the factors related to the growth of fire salamander larvae in different environmental conditions, evaluating the relationship between environmental features and larval growth and differences between caves and epigean spring habitats. Both caves and epigean larvae successfully grew. Capture-mark-recapture allowed to individually track individuals along their whole development, and measure their performance. Growth rate was significantly affected by environmental variables: larvae grew faster in environments with abundant invertebrates and few conspecifics. Taking into account the effect of environmental variables, larval growth was significantly lower in caves. Food availability plays a different effect in the two environments. Larval growth was positively related to the availability of invertebrates in epigean sites only. The development rate of hypogeous populations of salamanders is slower because of multiple parameters, but biotic factors play a much stronger role than the abiotic ones.